Wolves in Sheep's Clothing and Vice Versa: Fine-Needle Aspiration of Low-Grade Spindle Cell Lesions. Issue 2 (March 2022) - Bronson, Taylor; Choy, Bonnie
Abstract: The morphologic overlap between low-grade spindle cell lesions can lead to diagnostic dilemmas, particularly when attempting to interpret limited material. Evaluation of such specimens frequently requires correlating with clinical and imaging findings, as well as ancillary studies. We discuss the case of a 78-year-old woman with a remote history of breast carcinoma who presented with a left base of neck nodule. While imaging findings were highly suggestive of schwannoma, fine-needle aspiration biopsy of the nodule was performed for diagnostic confirmation. The patient reported tingling and an electrical shock sensation traveling down her arm during the fine-needle aspiration procedure. Cytomorphologic findings demonstrating a low-grade spindle cell neoplasm further supported a diagnosis of schwannoma, despite early immunohistochemistry results not being supportive. A last-minute suggestion that the differential diagnosis be broadened prompted additional immunohistochemical workup and follow-up molecular testing that confirmed an alternative diagnosis of solitary fibrous tumor. This case demonstrates the importance of correlating clinical, radiologic, and pathologic findings when approaching the differential diagnosis of low-grade spindle cell lesions on fine-needle biopsy specimens. Ancillary testing including immunohistochemistry, molecular studies, or fluorescence in situ hybridization is frequently utilized to establish a definitive diagnosis.